The Association Between Child Cooking Involvement in Food Preparation and Fruit and Vegetable Intake in a Hispanic Youth Population - Asigbee, Fiona M (Curr Dev Nutr, 2020)
BACKGROUND: Cooking interventions have been linked to reductions in obesity and improvements in dietary intake in children. OBJECTIVE: To assess whether child cooking involvement (CCI) was associated with fruit intake (FI), vegetable intake (VI), vegetable preference (VP), and vegetable exposure (VE) in children participating in the Texas, Grow! Eat! Go! (TGEG) randomized controlled trial. METHODS: Baseline data from TGEG included 1231 3rd grade students and their parents. Conducted in 28 low-income, primarily Hispanic schools across Texas, TGEG schools were assigned to: 1) Coordinated School Health (CSH) only (control group), 2) CSH plus gardening and nutrition intervention (Learn, Grow, Eat & Go! or LGEG group), 3) CSH plus physical activity intervention (Walk Across Texas or WAT group), and 4) CSH plus LGEG plus WAT (combined group). Height, weight, dietary intake, VE, VP, and CCI were collected at baseline and postintervention. Linear regressions were used to assess the relation between baseline CCI and fruit and vegetable (FV) intake, VE, and VP. A priori covariates included age, sex, race/ethnicity, and TGEG treatment group. RESULTS: Children who were always involved in family cooking had higher VP and VE when compared with children who were never involved in family cooking (β = 3.26; 95% CI: 1.67, 4.86; P < 0.01 and β = 2.26; 95% CI: 0.67, 3.85; P < 0.01, respectively). Both VI and FI were higher for children who were always involved in family cooking compared with children who never cooked with their family (β = 2.45; 95% CI: 1.47, 3.44; P < 0.01 and β = 0.93; 95% CI: 0.48, 1.39; P < 0.01, respectively). VI and fruit consumption were higher for children who reported being sometimes involved in family cooking compared with children who were never involved in family cooking, (β = 1.47; 95% CI: 0.51, 2.42; P < 0.01, and β = 0.64; 95% CI: 0.20, 1.08; P < 0.01, respectively). CONCLUSIONS: Results show a positive relation between family cooking and FV intake and preference in high-risk, minority children.